MODEL PEMBELAJARAN KREATIF PARTISIPATIF - OKI KURNIAWAN; ROSSI ISKANDAR (Jurnal Ilmiah Pendidikan Guru Sekolah Dasar, 2022)
Most educational studies on creativity tend to concentrate on explaining the relationship between teaching and creativity, creative teaching does not always lead to creative learning, the focus in much of the literature on creativity and teaching seems to be concentrated on teacher actions with less focus on the study of the learning process involved. actually among the students. This suggests the need to describe the concept of creative learning and analyze its possible constituents. Therefore, this article introduces an empirically based and theoretically informed creative learning community model. This model is based on learning principles that can take different forms in certain social settings and practices. These are respectively: (1) Participatory in the subject matter, (2) Experimental learning, and (3) Resistance to the material. As a theoretical starting point, this presentation will outline a model of creativity and learning.